2015
DOI: 10.1037/spq0000109
|View full text |Cite
|
Sign up to set email alerts
|

State learning disability eligibility criteria: A comprehensive review.

Abstract: For many decades, discussions regarding the definition and identification of learning disabilities have been contentious; one result is the varied practices across states and school districts. This study reviewed learning disability (LD) regulations and guidelines from the 50 United States and the District of Columbia that were employed during 2013. Two authors independently coded components of all LD regulations and guidelines. Results showed considerable variability in the state policies and practices govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
116
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 86 publications
(119 citation statements)
references
References 57 publications
2
116
1
Order By: Relevance
“…The results of this study in conjunction with previous research (e.g., Cottrell & Barrett, ; Reschly & Hosp, ; Maki et al, ) suggested a changing landscape in SLD identification. The declining, but still regular, use of ability–achievement discrepancy alongside the increasing use of PSW methods underscores the need for enhanced graduate training and professional development in SLD identification to support the implementation of evidence‐based practices to the maximum extent possible.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…The results of this study in conjunction with previous research (e.g., Cottrell & Barrett, ; Reschly & Hosp, ; Maki et al, ) suggested a changing landscape in SLD identification. The declining, but still regular, use of ability–achievement discrepancy alongside the increasing use of PSW methods underscores the need for enhanced graduate training and professional development in SLD identification to support the implementation of evidence‐based practices to the maximum extent possible.…”
Section: Resultssupporting
confidence: 86%
“…In addition to variable practices across states and over time, state special education regulations do not always provide a clear indication of the SLD identification practices in which states and LEAs engage. Oftentimes, state regulations provide limited information regarding how SLD identification methods should be implemented including a lack of operationalization of severe discrepancy, inadequate response, or a PSW, nor do state regulations comprehensively describe additional procedures for identification (e.g., classroom observations; Maki et al, ). Because state regulations are often limited in the extent to which they describe identification procedures, state departments of education frequently provide additional guidance outlining identification procedures (Maki et al, ).…”
Section: Sld Identification Methodsmentioning
confidence: 99%
See 3 more Smart Citations